Green Finance Education for Future Leaders: Embedding SDGs into Finance Curricula at Gulf University-Bahrain - Tanvir Mahmoud Hussein; Vinoth Raman (Universitas Diponegoro, 2025)
This research focuses on applying sustainable development principles to finance students’ education at Gulf University (GU)-Bahrain. We coincidentally emphasize the strategic alignment of the UN-SDGs to the finance curriculum. The research is a response to Bahrain’s Vision 2030 and the increasing regional focus on the sustainability of the economy. In this respect, GU paved the way for green finance and redefined finance education to upskill the graduates. Our mixed-methods approach involved analysis of finance program curricula, interviews with 18 faculty members, and surveys of 124 alumni and industry partners. Our research finds a successful three-pronged strategy. First, the finance curriculum was redesigned by SDG-aligned modules, which were embedded into core courses, replacing the traditional CSR course with ESG in Business. Second, partnerships with the Bahrain Association of Banks facilitated the co-development of ESG case studies and sustainability-oriented capstone projects. Third, faculty capacity building through programs such as green finance trainings since 2023 has upskilled 25+ instructors, resulting in a 67% increase in SDG-aligned research. The research highlights that GU's efforts have contributed to a 19% increase in finance graduates securing sustainability-aligned roles since 2023, aligning with Bahrain’s Vision 2030. This case study offers a blueprint for higher education institutions in the middle east keen to align finance education with sustainability. Finally, linking the university's action to measurable societal and economic impacts, GU demonstrates how higher education can align with national sustainability agendas while preparing graduates for global green finance markets.